Smart Pets Monitoring System Using Motion Sensor Based On IOT - mohd jais bin desa, shukrijais; Mohd Zainal, Dr Shamian bin mohd zainal (Progress in Engineering Application and Technology, 2021)
The purpose of this project is to develop a prototype system that can be used to detect pest’s movement such as monkey that entering the farms by using Smart Pests Monitoring System to protect the farms from the monkey that can steal and damage the crops. This system comprises of two parts, which are hardware and software. The development of The IOT Based Smart Pests Monitoring System based on the hardware unit such as IR sensor, NodeMCU ESP8266 and Speaker and software unit such as MQTT. IR Sensor is responsible to detect the movement of monkey to entering farms area. The NodeMCU being used to control the hardware part that can be programmed using NodeMCU ESP8266. After that, Speaker will be used to produce the sound of dog barking and lastly MQTT being used to send and receive data to the user. By implementing this Smart Pests Monitoring System, it allows farmers to experience an efficient smart pest monitoring system that can provide better and more effective security to protect farms from pests.